Thermoelectric Detection of Multi‐Subband Density of States in Semiconducting and Metallic Single‐Walled Carbon Nanotubes. Issue 25 (18th May 2016) - Shimizu, Sunao; Iizuka, Takahiko; Kanahashi, Kaito; Pu, Jiang; Yanagi, Kazuhiro; Takenobu, Taishi; Iwasa, Yoshihiro
Abstract : Thermoelectric detection of a multi‐subband density of states in semiconducting and metallic single‐walled carbon nanotubes is demonstrated by scanning the Fermi energy from electron‐doped to hole‐doped regions. The Fermi energy is systematically controlled by utilizing the strong electric field induced in electric‐double‐layer transistor configurations, resulting in the optimization of the thermoelectric power factor.